Telecommuting from the company perspective:employer intention to implement telecommuting - Mustafa Mohamed, Mustafa Mahdi (2012)
The Government of Malaysia is working hard to bring the country into a developed and industrialized country by the year,2020.To support this development companies in Malaysia have to prepare themselves toward virtual organization by implementing telecommuting as a tool.In other words companies in Malaysia are expected to play vies role for this task.The researchers argue that telecommuting offers significant benefits to employers,employees,but there no such research on employer intention (companies),are they willing to implement telecommuting? This research is very important in predicting employer intention to telecommute.Thus,the purpose of this study was to explore the employer intention to implement telecommuting in companies in Kuantan-Pahang,by looking at the factors that affect the employer intentions to implement telecommuting in their companies.Understanding the nature of these factors may assist companies in Malaysia to promote telecommuting as an alternative work.A survey was conducted using a structured questionnaire which distributed to 60 private companies.The result was indicated that the level of intention to telecommute was relatively high.Moreover the results showed employer attitudes toward telecommuting,pressure to use telecommuting,and perceived behavioural control are important factors in predicting employer intentions to implement telecommuting.he results also found that productivity and operating cost were not influenced the employer intention to implement telecommuting.Furthermore,it was found that attitude;subjective norms and perceived behavioural control were not mediated the relationship between productivity,operating cost and employer intention to implement telecommuting.Theory of planned behaviour (TPB)is the model widely used to discuss the effect of these antecedents in behavioural intention.An extension of employer intention with TPB would be in more comprehensive manner to understand behavioural intention to telecommute.